ANALISIS PEMERKOSAAN DALAM RUMAH TANGGA (MARITAL RAPE): SEBAB, MODUS OPERANDI, PERLINDUNGAN HUKUM TERHADAP KORBANNYA DAN UPAYA MENGATASINYA - Salsabila Anjani; Rajin Sitepu (LPPM Universitas Ekasakti Padang, 2023)
Marital Rape is something that makes a household unhappy, in fact it is a criminal act. Against this background, this research was conducted. This research is intended to reveal what causes the occurrence of Marital Rape, what is the modus operandi, how does the law protect victims and efforts to overcome them. This research is a normative juridical research in which data related to the Marital Rape problem are collected from library materials, both from journals, books and other library materials, the data obtained is then analyzed, identified, analyzed and concluded with inductive logic. The results of this study state that there are several reasons for Marital Rape, both direct causes, namely rejection by the wife; unbalanced libido and drunken husband. While the indirect causes are forced marriages; lack of communication and dependence of the wife because of economic difficulties. Furthermore, based on the analysis of several cases, the perpetrators tended to use violence and threats against the victim as well as threats of divorce so that the victim felt threatened and inevitably had to comply with the perpetrator's sexual desires regardless of the victim's condition. Legal protection for victims of Marital Rape has been regulated in a law, namely UU-TPKS. This law threatens to punish the perpetrators of Marital Rape. In addition, this law also regulates recovery efforts for victims of Marital Rape. Efforts that can be made to overcome cases of marital rape are as follows: Awareness and Education Raising; Effective Law Enforcement; Victim Support; Women empowerment; Collaboration between agencies.